Secondary Prevention of Cardiovascular Disease in Patients after Myocardial Infarction: Pharmacoepidemiological Study - Oxana Bogaevskaya (Journal of Global Pharma Technology, 2016)
Diseases of the cardiovascular system are among the main factors of premature death in the 21st century. However, the effectiveness of secondary prevention of coronary heart disease in developed Western countries and CIS countries can vary greatly. The purpose of this study is to evaluate the effectiveness of the application of international recommendations for secondary prevention in Russia in patients after myocardial infarction. The time of the study covers a 9-year period (2010-2019) in Cardiological Dispensary No. 3 of Moscow (Russia). A total of 9000 medical records were processed, of which 900 met the selection criteria. The average age of the patients was 61.5±9.7 years in an age range of 30-89 years. A survey of 606 doctors from private (1 group, 303 doctors) and state (2 groups, 303 doctors) dental clinics was conducted. Results the sample recorded a large scatter of data - from the moment the patient suffered a first heart attack - from a period of less than one year at a minimum to 43 years at a maximum. The average value of the interval was 4.6±5.3 years. Doctors on medical records most often paid attention to measuring blood pressure. 2-10 times less often (p≤0.001) met anthropometric indicators and analyzes for the lipid profile, and an order of magnitude less - control of the level of physical activity (p≤0.001). Differences were found between the therapy of patients depending on the type of medical institution - patients in cardiological dispensaries, on average, are 2-4 times more likely to receive prescription drugs (p≤0.001) compared with patients in polyclinics. It is noted that doctors, as a rule, do not note at the first visit to the patient in the cardiologic dispensary what kind of therapy he underwent in the clinic. It is necessary to promote a healthy lifestyle, with a complete cessation of smoking and the use of alcoholic beverages. This will minimize the cost of expensive drugs for the population. On the patient’s medical records: the minimum occurrence rates of the following risk factors were recorded: smoking (3%), as well as physical activity (less than 1%) and overweight (25%). Medications are rarely prescribed: anticoagulants in 1% of medical records, as well as statins (10%). The use of an articain-containing anesthetic with a vasoconstrictor concentration of 1:200000 or without a vasoconstrictor during dental surgery helps to prevent the risk of complications of the cardiovascular system, especially with prolonged dental surgery, and especially in patients at risk.Keywords: Myocardial infarction, Risk factors, Secondary prevention, Invasive therapy, Cardiovascular disease.